(untitled) (Neo Science Peer Reviewed Journal, 2023)
This article explores important aspects of the development of verbal and communicative competencies in students studying at pedagogical faculties. The authors analyze the factors that influence the formation of effective communication and teaching skills in future teachers. The study is based on a theoretical analysis of current psychological and pedagogical concepts, as well as on the results of our own empirical research, including observations, questioning and analysis of students’ practical classes. The article highlights the following key factors influencing the development of verbal and communicative competencies in future teachers: educational program and methodological support of the educational process, practical experience and mentoring support, motivation and psychological characteristics of students. The authors discuss the importance of reflection and self-assessment for improving verbal communication skills and offer practical recommendations for educational institutions and pedagogical practices aimed at optimizing the process of preparing future teachers for effective communication and learning.